Nutrient uptake, sugarcane yield and economics of high sugar early genotypes of sugarcane (Saccharum sp hybrid complex) under various planting seasons and fertility levels in Bihar - KUMAR, NAVNIT; SINGH, HARENDRA; KUMAR, RAKESH; KUMARI, GEETA (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted for 3 consecutive years (2006-2010) in two seasons (autumn and spring) on sandy loam soil of Bihar, Pusa (Samastipur), to find out the impact of early maturing high sugar genotypes and level of N-P and K fertilization on performance of sugarcane (Saccharum sp hybrid complex). The performance indicated significant superiority of CoSe 95422 to CoP 9301 in terms of germination (35.5 and 34.4 %), tillers (152 700 and 141 400/ha), cane length (204 and 201 cm) and cane diameter (2.32 and 2.25 cm) in autumn and spring season, respectively. CoSe 95422 exhibited significantly higher dry matter accumulation and leaf area index at all the growth stages during both the cropping seasons. Net assimilation rate increased substantially at the initial crop growth stages and declined thereafter. Genotype CoP 9301 achieved higher NAR (6.34 and 5.66 g/m2/day) during June- August, though it was failed to reach the level of significance during August-October. Number of millable canes exhibited marked variation among the genotypes in both the seasons. CoSe 95422 produced significantly highest cane yield during autumn (81.0 tonnes/ha) and spring season (73.2 tonnes/ha) respectively. The percentage increase in mean cane and sugar yield by autumn planted sugarcane over spring planted sugarcane was 9.7 and 11.27 %, respectively. However, maximum sugar yield was obtained by CoSe 95422. Further, it showed significantly higher N (206.8 and 176.5 kg/ha), P (18.5 and 16.9 kg/ha), K uptake (239.4 and 204.0 kg/ha), net return (` 55 430 and ` 46 500) and benefit: cost ratio (1.86 and 1.75) during autumn and spring season, respectively. Fertility level had significant impact on drymatter accumulation and leaf area index across the season as well as stages of growth. Significantly higher tillers (140 300 and 131 000/ha), cane length (208 and 204 cm), cane diameter (2.34 and 2.26 cm), millable cane (102 100 and 100 300/ha) and cane yield (85.2 and 77.6 tonnes/ha) were obtained with the application of 187.5 N + 46.4 P + 62.3 K kg/ha in autumn and spring season, respectively. Though all of these parameters except cane diameter in spring season were statistically similar to 150 N + 37.1 P + 49.8 K kg/ha. A significant increase in cane and sugar yield was observed up to 150 N + 37.1 P + 49.8 K kg/ha. The magnitude of increase in cane yield at 187.5 N + 46.4 P + 62.3 K, 150 N + 37.1 P + 49.8 K kg/ha over 112.5 N + 27.8 P + 37.4 K kg/ha were 37.6 and 30.9%, respectively, during autumn season. Whereas, these increased 35.7 and 28.0% respectively during spring season. Though, significant variation in sugar yield up to 150 N + 37.1 P + 49.8 K kg/ha was noticed during both the season. There was a significant increase in net return by increasing level of N+P+K/ha during both the season. Though, marked variation in benefit: cost ratio (1.87 and 1.75) was observed only up to 150 N + 37.1 P + 49.8 K kg/ha during autumn and spring season, respectively.